(untitled) (Scientific journal of the Fergana State University, 2023)
This study aimed to investigate the use of vocabulary learning strategies (VLS) and their effects on the development of students’ lexical knowledge, to identify the most and least used vocabulary learning strategies by the participants, and to improve students’ lexical competence. In order to find answers to the above questions, a questionnaire was taken from one hundred second year undergraduate students of Fergana State University. Participants answered the VLS questionnaire adapted from Schmitt’s (1997) taxonomy of vocabulary learning strategies. The results of the experiment showed that students preferred to use memory and metacognitive strategies in learning new words. The results of the study showed that the use of VLS has a positive effect on the development of lexical competence. Based on the results of the research, teachers and students were given appropriate suggestions to open the way to improve lexical knowledge.